Eksistensi Perempuan dalam Novel Tutur Dedes: Doa dan Kutukan Karya Amalia Yunus serta Pemanfaatannya sebagai Alternatif Materi Ajar Teks Esai di SMA - Dina Rohmawati (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This research aims to describe the manifestations of women's existence in the novel Tutur Dedes: Doa dan Kutukan by Amalia Yunus. This novel was chosen because the existence of female characters in the novel is clearly manifested. The existence of women in the novel is interesting to study because the subject is Ken Dedes, who in fiction is not told much other than as Ken Angrok's prameswari. This type of research is qualitative research using a feminist literary criticism approach. The data in this research are quotations in the novel that contain manifestations of women's existence. The data source is the novel Tutur Dedes: Doa dan Kutukan by Amalia Yunus. Data collection is done by using documentation technique with literature review approach. The data was analyzed using content analysis based on Simone De Beauvoir's theory of existentialist feminism. The results showed that there are manifestations of women's existence in the novel Tutur Dedes: Doa dan Kutukan in the form of (1) Women's existence as a subject manifested through the way female characters live their lives with firm faith, strong stance, courage, independence, loyalty, and against injustice. (2) The existence of women as intellectual figures manifested through the way female characters live their lives by having critical thinking, being wise, being able to apply their knowledge to everyday life, and having the ability to analyze the surrounding situation. (3) The existence of women as agents of social transformation is manifested through the way female characters change norms and culture, which initially women were not allowed to have skills in martial arts and weapons, it became normal for a woman to master these two things. The results of the study can be used as alternative literature teaching materials in high schools using the kurikulum merdeka with writing learning outcomes and essay text material.
Reaploud Repository February_Hasyim
Keywords: Women's existence; the novel Tutur Dedes: Doa dan Kutukan; existentialist feminism